Regulation of Kv4.2 A-Type Potassium Channels in HEK-293 Cells by Hypoxia - Liu, Yu-Qiang; Huang, Wen-Xian; Sanchez, Russell M.; Min, Jia-Wei; Hu, Jiang-Jian; He, Xiao-Hua; Peng, Bi-Wen (Frontiers in Cellular Neuroscience, 2014)
We previously observed that A-type potassium currents were decreased and membrane excitability increased in hippocampal dentate granule cells after neonatal global hypoxia associated with seizures. Here, we studied the effects of hypoxia on the function and expression of Kv4.2 and Kv4.3 α subunit channels, which encode rapidly inactivating A-type K currents, in transfected HEK293 cells to determine if hypoxia alone could regulate IA in vitro. Global hypoxia in neonatal rat pups resulted in early decreased hippocampal expression of Kv4.2 mRNA and protein with 6 or 12 hours post-hypoxia. Whole-cell voltage-clamp recordings revealed that similar times after hypoxia (1%) in vitro decreased peak currents mediated by recombinant Kv4.2 but not Kv4.3 channels. Hypoxia had no significant effect on the voltage-dependencies of activation and inactivation of Kv4.2 channels, but increased the time constant of activation. The same result was observed when Kv4.2 and Kv4.3 channels were co-expressed in a 1:1 ratio. These data suggested that hypoxia directly modulates A-type potassium channels of the subfamily typically expressed in principal hippocampal neurons, and does so in a manner to decrease function. Given the role of IA to slow action potential firing, these data are consistent with a direct effect of hypoxia to decrease IA as a mechanism of increased neuronal excitability and promotion of seizures.